PMO-076 Assessment of the probiotic symprove in patients with IBS: a randomised double blind placebo controlled trial. (28th May 2012) - Bjarnason, I; Sisson, G; Ayis, S
Abstract : Introduction: Treatment of patients with Irritable Bowel Syndrome (IBS) is often difficult, empiric and not evidence based. Recent insights into the pathogenesis of IBS have suggested that intestinal bacterial dysbiosis may result in symptomatic IBS. Accordingly, there is considerable interest in new treatments centred on modifying the intestinal bacterial flora with antibiotics or administration of appropriately designed probiotics. Therapeutic efficacy of probiotics appears to be strain specific. Symprove is a liquid probiotic formulation containing four bacterial strains ( Lactobacillus casei, acidophilus and plantarum as well as Enterococcus faecium ) with a shell life in excess of 3 months. We assessed its efficacy in patients with IBS. Methods: Material and Methods: This was a single centre, double blind, randomised, placebo controlled trial involving treatment with Symprove (1 ml/kg body weight) vs placebo for 3 months. Patients were recruited from two large GP practices and from GP referrals to the Department of Gastroenterology at King's College Hospital. All patients had failed conventional first and second line treatment by GP's. An initial 391 patients were screened for the trial and 186 were eligible and consented to the trial (fulfilled ROME III criteria, exclusion of organic disease by extensive investigation including intestinal permeability, faecal calprotectin, endoscopy, wireless capsule endoscopy, colonoscopy and radiology when indicated). Using the Mersenne twister pseudo-random number generator 124 received the active treatment and 62 placebo. The main outcome measure was the reduction in IBS symptom severity scores (IBS-SSS) at 3 months. All patients were symptomatic with IBS-SSS >150. Results: There were no significant differences between the two treatment groups with respect to demographic details (male/female ratio, mean age, duration of disease or previous treatment). There were no significant differences (p>0.1) at pre treatment IBS-SSS scores between active (303±68, mean±SD) and placebo (306±80) (p=0.841) treated patients. During the last week of treatment (week 12) there was a statistically significant (p<0.027) greater improvement in the mean IBS-SSS (230±109) in the Symprove treated patients as compared with placebo (270±103). The number of dropouts during the study did not differ significantly between the two groups and no severe adverse events were evident. Conclusion: Three months treatment with the probiotic Symprove was associated with significantly greater reduction in symptom severity in patients with moderate to severe IBS as compared with placebo. Competing interests: I Bjarnason grant/research support from: 3 year grant for MD student from the manufacturers of symprove, G Sisson grant/research support from: received 3 year salary from the manufactures of symprove, S Ayis: None declared.